Sustainable Tourism Appliance in Destinations: An Overview of Ghodaghodi Lake Area in Far West Nepal - Upadhayaya, Pranil Kumar (Contemporary Research: An Interdisciplinary Academic Journal, 2019)
Tourism is like a two edge sword which has both positive and negative consequences. Such a drift of tourism is found applicable in all destinations big or small, old or new. Nevertheless, the development intervention of new destinations with the sustainable tourism maxim from the very beginning can be much rewarding than a mass tourism induced mature destinations. Ghodaghodi Lake Area (GLA), a new tourist destination in Ghodaghodi Municipality (GM) of Kailali, extending to 2,726 hector of wetland with its designation as a Ramasar site, constitutes immense potential for prosperity through the sustainable tourism operation and management from its existing tourism offerings like lake viewing hiking, trekking, bird watching, and religious tourism activities. In this context, this paper aims to shed light on how a new destination like GLA is embedded with a number of challenges for sustainable tourism issues and what can be its remedy from sustainable tourism perspective. Developed through mix methods (qualitative and quantitative) of research, this paper has embedded its findings with the four progressive theoretical models (advocacy, cautionary, adaptability, and knowledge based platforms) as sustainable tourism. The poorly equipped infrastructures, lack of planned development activities, meager institutional capacity, and inadequate marketing have been pointed out as the drawback. This paper recommends that the formulation of a holistic plan of actions in the form of tourism master plan consisting of a self sustaining revenue model and its sincere application is the bottom-line to address sustainable tourism appliance challenges.